2010
DOI: 10.1002/jhm.516
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in a patient with cryptococcal meningitis: Syndrome of inappropriate antidiuretic hormone (SIADH) or cerebral salt wasting (CSW)?

Abstract: An 83-year-old man admitted for weakness, lethargy, and mental status changes was found to have human immunodeficiency virus (HIV) disease and cryptococcal meningitis. His hospital course was complicated by worsening hyponatremia (sodium < 136 mEq/L). By hospital day 6, the patient's serum sodium had declined to 127 mEq/L from his admission level of 133 mEq/L. The initial impression was that the patient had syndrome of inappropriate antidiuretic hormone (SIADH) and fluid restriction to less than 1500 mL per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…Consistent with previous studies, hyponatremia [16] was closely associated with the occurrence of CM. The underlying mechanism connecting hyponatremia with CM is unclear.…”
Section: Clinical Features and Risk Factorssupporting
confidence: 92%
“…Consistent with previous studies, hyponatremia [16] was closely associated with the occurrence of CM. The underlying mechanism connecting hyponatremia with CM is unclear.…”
Section: Clinical Features and Risk Factorssupporting
confidence: 92%
“…Previous studies have suggested that some CNS infections, such as cryptococcal meningitis [39] or tuberculosis meningitis [40], [41] result in a low serum sodium concentration. Pneumonia is also a common reason for the development of hyponatremia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Подобная картина транзиторного ухудшения неврологической симптоматики на фоне положи-тельной динамики лабораторных показателей описана у боль-ных с КМЭ и ВИЧ-инфекцией после начала антиретровирус-ной терапии [9].…”
Section: Discussionunclassified